'Green growth' is called into question - Coutrot, Thomas; Gadrey, Jean (Brussels, 2012)
"In this Policy Brief the authors put in question the possibility, generally accepted without justification or context, of pursuing growth while respecting ‘vital’ constraints of the environment. Instead, they argue, there are credible alternative ‘post-growth’ strategies, aimed at ‘sustainable prosperity without growth’, which might be more conducive to employment and equality than the current ‘productivist’ trajectory."